2020
DOI: 10.22441/mix.2020.v10i2.004
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Profitabilitas, Struktur Modal, Dan Keputusan Investasi Terhadap Nilai Perusahaan (Pada Sektor Farmasi Yang Terdaftar Di Bursa Efek Indonesia Tahun 2013-2017)

Abstract: This study aims to determine the effect of Profitability, Capital Structur, and Investment Decision to company values. This population is pharmacist companies of Indonesia Stock Exchange on periode 2013 to 2017. The research design is causal research. The sampling technique is purposive sampling method. The method derived 6 companies that meet the criteria from 9 companies during the observation period of five years. Total sampel are 30 sample. The analysis technique used is the panel data regression. The resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
1
8

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 7 publications
1
8
1
8
Order By: Relevance
“…Firm value is the company's performance which is reflected in the share price formed by the supply and demand of the capital market which reflects the social assessment of the company's performance (Oktiwiati & Nurhayati, 2020). In research profitability is measured using Price to Book Value (PBV) (Basri & Multama, 2021).…”
Section: Firm Valuementioning
confidence: 99%
See 1 more Smart Citation
“…Firm value is the company's performance which is reflected in the share price formed by the supply and demand of the capital market which reflects the social assessment of the company's performance (Oktiwiati & Nurhayati, 2020). In research profitability is measured using Price to Book Value (PBV) (Basri & Multama, 2021).…”
Section: Firm Valuementioning
confidence: 99%
“…One of the efforts made by the company is to enter the capital market, so that it becomes easier to get an injection of funds. This has an impact on more and more investors who are interested in investing in companies that are in the capital market (Oktiwiati & Nurhayati, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Ketika nilai perusahaan tinggi, maka menandakan bahwa perusahaan tersebut memiliki kinerja perusahaan yang baik (Haryanto, 2014;Kusuma, 2018;Jemunu et al, 2020;dan Bakhtiar et al, 2021). Nilai perusahaan merupakan cerminan dari ekspektasi investor terhadap suatu perusahaan (Solikahan et al, 2013;Yu & Zhao, 2015;Haryanto et al, 2018;Oktiwiati & Nurhayati, 2020;Hasanuddin et al, 2021).…”
Section: Pendahuluanunclassified
“…Then from the ROE variable, different research results were obtained, as in the research that was conducted by Sondakh, et al (2019) and Ali et al (2021) find that ROE positively and significantly affects firm value, while different results were obtained by Tanjung and Halawa (2022) reveals that ROE does not affect firm value. Furthermore, from the capital structure variable, different results were obtained, such as research conducted by Oktiwiati and Nurhayati (2020) and Julaeha, et al (2021) find that capital structure positively and significantly affects firm value, while the results different results were obtained by Haq and Rahayu (2019) and Fitriyah and Djawoto (2021) reveals that capital structure does not affect firm value. Then the same thing happens to the investment decision variable, where Haq and Rahayu (2019) and Oktiwiati and Nurhayati (2020) find that investment decision positively and significantly affects firm value, while Amaliyah and Herwiyanti (2020) and Salama, et al (2019) which found that investment decisions did not affect firm value.…”
Section: Introductionmentioning
confidence: 97%
“…Furthermore, from the capital structure variable, different results were obtained, such as research conducted by Oktiwiati and Nurhayati (2020) and Julaeha, et al (2021) find that capital structure positively and significantly affects firm value, while the results different results were obtained by Haq and Rahayu (2019) and Fitriyah and Djawoto (2021) reveals that capital structure does not affect firm value. Then the same thing happens to the investment decision variable, where Haq and Rahayu (2019) and Oktiwiati and Nurhayati (2020) find that investment decision positively and significantly affects firm value, while Amaliyah and Herwiyanti (2020) and Salama, et al (2019) which found that investment decisions did not affect firm value. As well as from the firm size variable the same thing also occurs, where in research conducted by Yuniastri, et al (2021) and Haq and Rahayu (2019) find that firm size positively and significantly affects firm value, while Wahyuni and Purwaningsih (2021) and Nasution (2021) reveals that firm size does not affect firm value.…”
Section: Introductionmentioning
confidence: 97%